2021
DOI: 10.3390/ijms222212340
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Control of Apical-Basal Polarity Regulators

Abstract: Cell polarity is essential for many functions of cells and tissues including the initial establishment and subsequent maintenance of epithelial tissues, asymmetric cell division, and morphogenetic movements. Cell polarity along the apical-basal axis is controlled by three protein complexes that interact with and co-regulate each other: The Par-, Crumbs-, and Scrib-complexes. The localization and activity of the components of these complexes is predominantly controlled by protein-protein interactions and protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 97 publications
(141 reference statements)
1
3
0
Order By: Relevance
“…Consistent with this potential role, SP family TFs were more highly bound to upstream promoter regions of several genes such as PPP2R1B and LLGL1 involved in establishing epithelial apical-basal polarity (Fig. 5H) (59,62,63). The RNA-seq data corroborated these findings, as multiple upregulated genes with known SP family target sites were differentially expressed in normal versus abnormal polarity organoids (Fig.…”
Section: Sequencing Of Abnormal Versus Normal Polarity Organoids Reve...supporting
confidence: 66%
See 1 more Smart Citation
“…Consistent with this potential role, SP family TFs were more highly bound to upstream promoter regions of several genes such as PPP2R1B and LLGL1 involved in establishing epithelial apical-basal polarity (Fig. 5H) (59,62,63). The RNA-seq data corroborated these findings, as multiple upregulated genes with known SP family target sites were differentially expressed in normal versus abnormal polarity organoids (Fig.…”
Section: Sequencing Of Abnormal Versus Normal Polarity Organoids Reve...supporting
confidence: 66%
“…At a molecular level, transcription factor (TF) footprinting analysis of the ATAC-seq data indicated that organoids with abnormal polarity had increased accessibility in chromosomal regions bound by the SP family TFs (Fig. 5G), which are involved in maintaining epithelial cell polarity (58,59) and are dysregulated in a variety of cancer types (60,61). Consistent with this potential role, SP family TFs were more highly bound to upstream promoter regions of several genes such as PPP2R1B and LLGL1 involved in establishing epithelial apical-basal polarity (Fig.…”
Section: Sequencing Of Abnormal Versus Normal Polarity Organoids Reve...mentioning
confidence: 99%
“…Furthermore, NKCC2 phosphorylation was significantly decreased in Umod -/- mice ( 38 ). Because apical expression and phosphorylation are essential for the membrane protein function ( 39 ), the downregulation of apical expression and phosphorylation of NKCC2 in Umod -/- mice indicates defective transporter activation. The loss of function of NKCC2 generates a phenotype similar to Bartter syndrome, a salt-losing tubulopathy.…”
Section: Functions Of Uromodulinmentioning
confidence: 99%
“…Metazoan epithelial cells, highly polarized along their apico‐basal (A/B) axis, connect with each other via a variety of inter‐cellular junctions and the polarization is critical for the structure and functions of the epithelial tissues they comprise 1–10 . Disruption of epithelial polarity is often associated with tumorigenesis and metastasis 11,12 . The epithelial plasma membranes are divided into distinct domains along their A/B axis.…”
Section: Introductionmentioning
confidence: 99%